Water availability and climatic water balance for a selected cropped area - Venkata Sai, K (Department of Irrigation and Drainage Engineering, Kelappaji College of Agricultural Engineering and Technology, 2018)
Rainfall is the main source available for water. The knowledge of the rainfall analysis is crucial for crop planning in a region and designing of water conservation structures. The changes in rainfall, its distribution, probability and trends would influence the spatial and temporal distribution of runoff, soil moisture and groundwater reserves. Crop production in an area has a direct relation with the amount and distribution of rainfall. So correct evaluation of water availability period is an important pre-requisite for crop planning. Climatic water balance is widely used for determining the water surplus, water deficit and water availability period for agricultural planning. Hence in the present research work, the rainfall data of Pattambi was analysed to study the variability, trends and probability of rainfall. A weekly climatic water balance was also assessed to determine the surplus/deficit of rainwater. The rainfall variability analysis showed that the mean annual rainfall of Pattambi region was found 2377.96 mm with a CV of 19.29 % which indicated that the rainfall is highly stable in the region. The South-West monsoon season contributed the highest (74.09 %) amount of rainfall. June and July were the months recorded the highest percentage of rainfall of 25.39 % and 24.06 % respectively. Weekly rainfall variability showed that rainfall was stable during 21st to 45th SMWs as the CV ranges from 90 % to 110 % only. The trend analysis of annual, seasonal and monthly rainfall according to Mann-Kendall test revealed that there was a rising and falling trends. But there was no significant trend observed at 5 % level of significance except in summer season. The Sen’s slope estimator revealed that a rising trend was observed in summer season whereas falling trend was observed in annual, South-West and North-East monsoon season and no trend was observed at winter season. The rainfall probability at different levels of exceedance were found by fitting “Incomplete gamma distribution” using Weather Cock software. The weekly rainfall probability at 75 % level of exceedance varied from 10.3 to 72.6 mm during the weeks 21st to 46th. The highest monthly rainfall at 75 % exceedance occurred during June (471.1 mm) and lowest during January (3.1 mm). The highest seasonal rainfall at 75 % exceedance occurred during South-West monsoon (1466.4 mm) and lowest during winter season (10.8 mm). The annual rainfall at 75 % level of exceedance was found to be 2051.6 mm. Weibull distribution was identified as the best fit for weekly rainfall distribution in the region. The total ETc demand of rice, banana and vegetable crops at 50 % probability levels of ETo was estimated as 469.162 mm, 1124.81 mm and 267.92 mm whereas the rainwater availability at 75 % probability level was 933.85 mm, 1107.53 mm and 59.18 mm respectively. It was observed that there was a surplus of 464.688 mm for rice, deficit of 17.28 mm for banana and deficit of 208.74 mm for vegetable crop. The climatic water balance indicated that water surplus (SUR) and water deficit (DEF) components are significant. The total climatic water surplus and deficit in the region was estimated as 1985.54 mm and 155.08 mm. The Moisture Adequacy Index (MAI) of the region indicated that the most of the weeks were of in good potential for growing crops. The determination of water availability period revealed that 1,4,5,8, 9, 11 and 50th SMWs were in water deficit whereas the remaining weeks were in water surplus.